Improved 1H body imaging at 10.5 T: Validation and VOP‐enabled imaging in vivo with a 16‐channel transceiver dipole array - Schmidt, Simon; Ertürk, M. Arcan; He, Xiaoxuan; Haluptzok, Tobey; Eryaman, Yiğitcan; Metzger, Gregory J. (Magnetic resonance in medicine, 2024)
Purpose To increase the RF coil performance and RF management for body imaging at 10.5 T by validating and evaluating a high‐density 16‐channel transceiver array, implementing virtual observation points (VOPs), and demonstrating specific absorption rate (SAR) constrained imaging in vivo. Methods The inaccuracy of the electromagnetic model of the array was quantified based on B1+ and SAR data. Inter‐subject variability was estimated using a new approach based on the relative SAR deviation of different RF shims between human body models. The pTx performance of the 16‐channel array was assessed in simulation by comparison to a previously demonstrated 10‐channel array. In vivo imaging of the prostate was performed demonstrating SAR‐constrained static RF shimming and acquisition modes optimized for refocused echoes (AMORE). Results The model inaccuracy of 29% and the inter‐subject variability of 85% resulted in a total safety factor of 1.91 for pelvis studies. For renal and cardiac imaging, inter‐subject variabilities of 121% and 141% lead to total safety factors of 2.25 and 2.45, respectively. The shorter wavelength at 10.5 T supported the increased element density of the 16‐channel array which in turn outperformed the 10‐channel version for all investigated metrics. Peak 10 g local SAR reduction of more than 25% without a loss of image quality was achieved in vivo, allowing a theoretical improvement in measurement efficiency of up to 66%. Conclusions By validating and characterizing a 16‐channel dipole transceiver array, this work demonstrates, for the first time, a VOP‐enabled RF coil for human torso imaging enabling increased pTx performance at 10.5 T.